El desarrollo socio-afectivo generado por la influencia de la dramatización en los niños y niñas del nivel de educación inicial 2 paralelos “A” y “E” de la Unidad Educativa “Vicente León” de la parroquia Juan Montalvo, cantón Latacunga, provincia de Cotopaxi en el año lectivo 2014-2015 - Esquivel Zambrano, Silvana Estefanía (2015)
The present research was made with the main objective to help Vicente Leon Educative Unit kids of second initial level class A and E in reason that these classes have a big number of students with socialization problems, without social expression where they are scared to be hurt or criticize for other ones, for this reason it was necessary developing an investigation in way to get better Social Affective Area through: dramatization, ludic and creative activities where children could be the protagonist of their learning, communication and expression processes using these ways to get better affectivity and teachers, parents and kids satisfaction was possible, to obtain results different techniques were applied as interview, observation sheet where the information proved the importance of this job, taking count a manual implementation was able to improve dramatization to increase inside class student’s socialization, it lets a personal and academic performance between them.